Ponieważem się już obiecał… Ruchome końcówki czasownika w czasie przeszłym - Anna Dąbrowska (Postscriptum Polonistyczne)
The article discusses the examples of movable past verbs’ suffixes and their usages as described in four old manuals for teaching Polish as a foreign language. They have been confronted with the results of T. Rittel’s and A. Kowalska’s research, which proves that the authors of the old manuals reflected the Polish language of their times in their textbooks. They usually give one form of the past verb, treating it as a model, which was well justified in the case of a spoken language.